A Review and Taxonomy of Image Denoising Techniques - Jebur R.S.; Der C.S.; Hammood D.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Convolution; Digital storage; Fuzzy sets; Human computer interaction; Image enhancement; Mean square error; Median filters; Neural networks; Convolution neural network; De-noising techniques; Non-local filters; Non-local mean filters; Peak signal noise ratio; Root mean square errors; Structure similarity; Wavelet threshold; Image denoising